Anti-cancer effects of ethanol extract of Reynoutria japonica Houtt. radix in human hepatocellular carcinoma cells via inhibition of MAPK and PI3K/Akt signaling pathways. (5th December 2019) - Kim, Ba Reum; Ha, Jain; Lee, Sewoong; Park, Jiyoung; Cho, Sayeon
Abstract: Ethnopharmacological relevance: Reynoutria japonica Houtt. has been used as a traditional medicine of cancer in East Asia for thousands of years. However, the mechanism of the anti-cancer effect of R. japonica has not been investigated at the molecular level. The regulation of intracellular signaling pathways by the extract of R. japonica radix needs to be evaluated for a deeper understanding and application of the anti-cancer effect of R. japonica radix. Aim of the study : The purpose of this study was to evaluate the inhibitory effects of the ethanol extracts of R. japonica radix (ERJR) on cancer metastasis and the regulation mechanism of metastasis by ERJR in human hepatocellular carcinomas. Materials and methods: Suppression of cancer metastasis by ERJR in SK-Hep1 and Huh7 cells were investigated. Prior to experiments, the cytotoxic effect of ERJR was examined by cell viability assays. To evaluate the inhibitory effects of ERJR on cancer metastasis, wound-healing assays, invasion assays, zymography, and multicellular tumor spheroids (MCTS) assays were performed. Molecular mechanisms in the suppressive regulation of metastasis by ERJR were verified by measuring the expression levels of metastatic markers, and the phosphorylation and protein levels of cancer metastasis-related signaling pathways. Results: In all experiments, ERJR was used at a maximum concentration of 20 μg/ml, which did not show cytotoxicity in SK-Hep1 and Huh7 cells. We examined the inhibitory effects of ERJR on cancer metastasis. In wound-healing and invasion assays, ERJR treatment effectively suppressed the wound-recovery of Huh7 cells and inhibited the invasion ability of SK-Hep1 cells. Also, ERJR treatment significantly decreased the enzymatic activity of matrix metalloproteinase-2 and -9 in SK-Hep1 cells. ERJR suppressed the growth of MCTS in SK-Hep1 cells in a dose-dependent manner. These results indicated that ERJR effectively inhibited the invasive and proliferative ability of SK-Hep1 and Huh7 cells. Moreover, ERJR treatment reduced the expression levels of Snail1, Twist1, N-cadherin, and Vimentin, which are metastatic markers, by inhibiting the activation of protein kinase B and mitogen-activated protein kinases in SK-Hep1 cells. Conclusions: These results verified the molecular mechanism of ERJR that has been used in traditional anti-cancer remedy and suggest that it can be developed as a promising therapy for cancer metastasis in the future. Graphical abstract: Image 1